Exploring Pre-Service English Teachers’ Sentiments and Concerns Toward Inclusive Education - Sheilamitha Amanda; Khusnul Khatimah; Dzul Rachman (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study explores pre-service English teachers’ sentiments and concerns toward inclusive education in the Indonesian EFL context. Grounded in the Theory of Planned Behavior, the study examines affective readiness by focusing on two dimensions measured through the SACIE-R instrument: sentiments and concerns, which provide more specific insights into emotional acceptance and perceived implementation challenges than general attitude measures. A descriptive quantitative design was employed, involving 40 pre-service English teachers from Universitas Muhammadiyah Kalimantan Timur who had completed the Inclusive Education course. Data were collected using a modified version of the SACIE-R questionnaire and analyzed using descriptive statistics. The findings indicate that pre-service teachers demonstrated low to moderate positive sentiments toward inclusive education, suggesting cautious acceptance accompanied by lingering emotional discomfort and uncertainty when interacting with students with disabilities. In addition, a moderate level of concern was identified, particularly related to pedagogical competence, classroom management, peer acceptance, and availability of instructional resources. These patterns reveal a gap between cognitive awareness of inclusive principles and emotional as well as practical readiness for classroom implementation. The study highlights the need for stronger experiential learning opportunities, structured practicum exposure, and institutional support within teacher education programs to strengthen affective readiness and build confidence in managing inclusive classrooms.